Pengaruh Motivasi Berwirausaha dan Pengetahuan Kewirausahaan Terhadap Keberhasilan Usaha pada Multiguna Forklift - Dedy Lazuardi (Forum Kerjasama Pendidikan Tinggi, 2024)
This study aims to determine the effect of Entrepreneurial Motivation on Business Success on Multipurpose Forklifts, determine the effect of Entrepreneurial Knowledge on Business Success on Multipurpose Forklifts, determine the effect of Entrepreneurial Motivation and Entrepreneurial Knowledge on Business Success on Multipurpose Forklifts. The research methodology used is descriptive quantitative method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers or numbers. Sources of data in the form of primary data and secondary data. Primary data was obtained from the results of distributing questionnaires to respondents, secondary data was obtained from data and literature relating to the problems discussed. In this study, the population is the forklift business in Multi-Use Forklift as many as 30 respondents. By using a saturated sample, the number of samples obtained is 30 respondents. Data were analyzed using multiple linear regression analysis method. The results showed that Entrepreneurial Motivation and Entrepreneurship Knowledge had a positive and significant effect on Business Success on Multipurpose Forklifts.In conclusion, monetary policy plays a significant role in determining interest rates and maintaining economic stability. Central banks need to consider broader economic conditions and adopt a flexible and responsive approach to changes in both domestic and global economies.